The Role of Extracellular Vesicles in the Pathogenesis and Treatment of Autoimmune Disorders - Lu, Mengrou; DiBernardo, Emma; Parks, Emily; Fox, Hannah; Zheng, Si-Yang; Wayne, Elizabeth (Frontiers in Immunology, 2021)
Extracellular vesicles (EVs) are important players in autoimmune diseases, both in disease pathogenesis and as potential treatments. EVs are capable of both transport and communication, and EVs from stressed cells communicate with immune cells via the presentation of autoantigens. EVs are involved in the initiation and progression of autoimmune diseases, and a better understanding of EVs will allow us to have a deeper understanding of the pathogenesis of these diseases. In addition, EVs can also be effective treatments for autoimmune diseases. The diversity of cell types that produce EVs leads to a wide range of molecules to be present in EVs, and thus EVs have a wide range of physiological effects. EVs derived from dendritic cells or mesenchymal stem cells have been shown to reduce inflammation. Since many autoimmune treatments are focused only on symptom management, EVs present a promising avenue for potential treatments. This review looks at the different roles EVs can play in autoimmune diseases, from disease pathology to diagnosis and treatment. We also overview various methodologies in isolating or generating EVs and look to the future for possible applications of EVs in autoimmune diseases.